Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.toxrep.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects of Lambda-cyhalothrin, on the rat thyroid: Involvement of oxidative stress and ameliorative effect of ginger extract

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 73 publications
4
18
0
Order By: Relevance
“…In the current study, terminal body weight and relative weight of liver of LCT-intoxicated rats were reduced that run in a good agreement with previous studies [14,[45][46][47][48]. Elhalwagy et al [1] demonstrated that decreasing body weight and organs relative weight is one of the chronic effects of pyrethroids toxicity.…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, terminal body weight and relative weight of liver of LCT-intoxicated rats were reduced that run in a good agreement with previous studies [14,[45][46][47][48]. Elhalwagy et al [1] demonstrated that decreasing body weight and organs relative weight is one of the chronic effects of pyrethroids toxicity.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, Al-Amodie stated that ginger extract improved the histochemical and histological changes of the thyroid gland induced by insecticide Lambda-cyhalothrin. Furthermore; it increased T3 and T4 and decreased TSH hormones levels, decreased MDA level the lipid peroxidation marker and increased the antioxidant enzymes (25) .Another study revealed the ameliorative role of ginger extract on the insecticide mancozeb toxicity of the thyroid gland in rats (26) . Yousef et al .suggested that administration of ginger extract was a valuable routine for protection in opposition to the damaging effect of cypermethrin in the thyroid gland structure (10) .Other study proved that the antioxidative, anti-inflammatory and antiapoptotic functions were the most effective role of ginger in protection against chlorpyrifos toxicity in the brain and reproductive organs of rats (27) .…”
Section: Discussionmentioning
confidence: 93%
“…The level of SOD, Catalase, GSH also showed significant perturbations in rat liver while on of Citrus limon fruit extract markedly ameliorated the toxicity of Carbofuran by protecting the levels of the aforementioned biomarkers to near the control level [19]. Al- [20] reported the protective role of ginger on Lambda cyhalothrin (LC) insecticide, a decrease in SOD and CAT but an increase in the cyhalothrin induced toxicity while LC plus ginger increased the antioxidant enzymes and decreased MDA Cyhalothrin may not have obvious effect on the organ weights, body weight and gonadosomatic indices but silently destroy target cells of the body overtime. A comparison of the trend in liver biomarkers, histopathological analysis of the liver vealed Cyhalothin induce oxidative and reproductive stress in exposed animals while results from groups co-administered Citrullus lanatus and Annona muricata revealed the therapeutic role this indigenous fruit on Cyhalothin-induced toxicity and therefore should be used as Supplement and a suitable first aid for pesticide related poisoning.…”
Section: Resultsmentioning
confidence: 99%
“…The level of SOD, Catalase, GSH also showed significant perturbations in rat liver while administration of Citrus limon fruit extract markedly ameliorated the toxicity of Carbofuran by protecting the levels of the aforementioned biomarkers to near the control level [19]. Amoudi [20] reported the protective role of ginger on Lambda cyhalothrin (LC) inse decrease in SOD and CAT but an increase in the levels of MDA in lambda-cyhalothrin induced toxicity while LC plus ginger increased the antioxidant enzymes and decreased MDA levels.…”
Section: Potential Reproductive Toxicity By Histopathological Analysimentioning
confidence: 99%